2002
DOI: 10.1136/bmj.324.7337.594
|View full text |Cite
|
Sign up to set email alerts
|

ABC of clinical electrocardiography: Atrial arrhythmias

Abstract: tion strategies. 16 Over the 12 months after randomisation, the total cost of consultations, referrals, investigations, and treatment was on average £404.31 in the endoscopy group compared with only £205.67 in the non-invasive H pylori testing group. Two smaller studies have compared H pylori testing with endoscopy in subgroups of patients with dyspepsia referred for endoscopy. 4 6 No differences were found between the two investigation strategies with respect to resolution of dyspepsia, use of drugs, or visit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Atrial fibrillation (AF) is an arrhythmia characterized by abnormal and chaotic electrical pulse generation observed in the upper heart chambers (Goodacre & Irons, ). This condition is the most common heart rhythm disorder, with prevalence rates of 2.3‐3.4% in the general population (Friberg & Bergfeldt, , ; Wilke et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Atrial fibrillation (AF) is an arrhythmia characterized by abnormal and chaotic electrical pulse generation observed in the upper heart chambers (Goodacre & Irons, ). This condition is the most common heart rhythm disorder, with prevalence rates of 2.3‐3.4% in the general population (Friberg & Bergfeldt, , ; Wilke et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…We also identified patients with self-terminating ATAs and lasted >30 s on ICD interrogation. ATAs were classified as ATs if regular atrial waves of 100–250 bpm with a regular ventricular rhythm (variable ventricular rate) were observed, as AFLs if the regular baseline atrial rhythm was observed as flutter waves of 250–350 bpm with a regular ventricular rhythm (usually with an atrioventricular block) or as AFs if an irregular baseline atrial rhythm was observed as fibrillation waves with an irregular ventricular rhythm [15] . ATAs appearing only during electrophysiologic studies, atrioventricular nodal reentrant tachycardia or atrioventricular reentrant tachycardia were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…P-wave morphology may be different from sinus beats and varies depending on the origin of the impulse in the atria. In some cases, P waves are even missing in APB, because consecutive T and P waves overlap [8].…”
Section: Introductionmentioning
confidence: 98%
“…Thus, APB can also be detected by means of heart rate variability (HRV) analysis. If the premature excitation is abrupt, there is a delay in sinusal node activation for the next cardiac cycle, which causes an alternating increase-decrease heart rate [8]. When the premature excitations are sustained in time, this alternating pattern disappears and turns into a constant raised heart rhythm.…”
Section: Introductionmentioning
confidence: 98%